A method for removing titanium nitride coating on the surface of glass forming mold and recovering titanium element
By using a removal liquid composed of hydrogen peroxide and ammonia triacetic acid complexing agent, the problems of high risk, long deplating time and environmental pollution in the existing titanium nitride coating removal methods are solved, and safe and efficient removal and recycling of titanium elements are achieved.
Patent Information
- Application Number
- CN202211464269.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-22
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2042-11-22
AI Technical Summary
The existing titanium nitride coating removal methods have problems such as high risk, long deplating time, easy corrosion of the substrate, environmental pollution, limited complexing capacity of alkaline removal liquids, and poor removal efficiency.
The removal solution consisting of hydrogen peroxide and ammonia triacetic acid complexing agent was used to remove the titanium nitride coating on the surface of the glass molding mold through the impregnation reaction, and the titanium element was recovered through subsequent treatment.
It realizes safe and efficient removal of titanium nitride coating, avoids matrix corrosion and environmental pollution, and improves the removal efficiency and titanium recovery rate.
Smart Images

Figure CN115637436B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of titanium nitride hard coating removal on a mold surface, and in particular to a method for removing titanium nitride coating on a glass forming mold surface and recovering titanium elements. Background Art
[0002] The information disclosed in the background of the present invention is only intended to increase the understanding of the overall background of the present invention and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Plating titanium nitride (TiN) hard coating on the surface of stainless steel glass forming molds can effectively improve the surface mechanical properties, anti-friction and anti-oxidation capabilities of the molds, thereby meeting the needs of glass product molding. However, with the long-term use of the mold, the surface coating often becomes damaged and aged, affecting the glass molding effect. In order to reuse the mold, the surface damaged coating needs to be completely removed and then re-plated. With the complexity of mold shapes and the diversification of coating processes, higher requirements are placed on the development of film removal technology.
[0004] At present, the titanium nitride hard coating stripping technology can be roughly divided into the following three categories: the first one is the chemical stripping method, which is to etch and strip the hard film through the redox reaction between the acidic or alkaline stripping solution and the coating material. The advantages of this method are simple process, no restrictions on the mold shape and uniform stripping. The disadvantages are that the improper use of strong acids (hydrofluoric acid, nitric acid) or strong bases (sodium hydroxide, potassium hydroxide) can easily cause corrosion to the stainless steel mold substrate; in addition, after the stripping is completed, the titanium nitride hard coating will be etched and stripped. 2+ 、Ti 3+ 、Ti 4+ The stripping waste liquid containing metal ions is difficult to treat and can easily cause environmental pollution. The second method, the electrolytic stripping method, uses the principle of the electrolytic cell to place the stripping mold, inert electrode and reference electrode in the electrolyte, constructs a two-electrode or three-electrode reaction system, and realizes the stripping of the hard coating by electrochemical oxidation-reduction. Compared with the chemical stripping method, this electrochemical stripping technology has the advantages of rapid response and thorough stripping. However, the construction of the electrolytic cell will undoubtedly increase the production cost, and the voltage range and current density must be strictly controlled during the reaction process, otherwise the substrate will also be corroded, which makes the stripping process more complicated. The third method, the mechanical polishing method, is to remove the coating by mechanical grinding. In this way, the process is the simplest and avoids the use of chemical reagents, but the stripping time is long and it cannot be applied to complex molds, which has great limitations in practical applications.
[0005] Chemical stripping is the most commonly used method by enterprises at present. The alkaline stripping solution used is a mixture of hydrogen peroxide and sodium hydroxide, while the acidic stripping solution used is a mixture of nitric acid and hydrofluoric acid in a volume ratio of 1:1. Both methods can achieve the stripping of titanium nitride coating. However, as mentioned above, both alkaline and acidic solutions are corrosive to the stainless steel mold substrate, especially the acidic solution system can react quickly with the Fe, Cr, and Ni elements in the stainless steel substrate. Although the alkaline solution system is much weaker than the acidic solution in corrosiveness to the stainless steel substrate, the large amount of heat released during the addition of sodium hydroxide will accelerate the decomposition of hydrogen peroxide, which not only reduces the oxidation effect of the stripping solution, but also easily causes burns if it is improperly operated. In order to improve the stability of the alkaline stripping solution and increase the stripping rate, complexing agents (citric acid, phosphate, ethylenediaminetetraacetic acid, etc.) are introduced into the reaction system (patents CN101570860A, CN103046052A and CN105018934A). However, there are still shortcomings such as limited complexing ability and unsatisfactory stripping efficiency. In addition, the current processes all focus on the coating stripping effect and ignore the treatment of titanium ion-containing stripping waste liquid. This patent starts from the physical and chemical properties of titanium nitride hard film and mold substrate and combines the research on stripping mechanism to construct titanium nitride coating stripping liquid and corresponding technology with rapid stripping, no damage to the substrate, simple components and low cost in order to solve this problem. At the same time, this patent combines national environmental protection requirements and the production concept of turning waste into treasure to post-treat the stripping waste liquid to achieve the recovery of metal elements, in order to establish a green and highly recycled production process model. Summary of the invention
[0006] In view of the problems existing in the current method for stripping titanium nitride coating, such as high risk, long stripping time, easy corrosion of substrate, environmental pollution, limited complexing ability of alkaline stripping solution, and poor stripping efficiency, the present invention provides a method for stripping titanium nitride coating on the surface of glass forming molds and recovering titanium element, which can safely and efficiently strip the titanium nitride coating on the surface of glass forming molds.
[0007] The present invention is achieved through the following technical solutions:
[0008] A method for removing titanium nitride coating on the surface of a glass forming mold comprises immersing the glass forming mold with titanium nitride coating in a stripping solution composed of hydrogen peroxide and nitrilotriacetic acid complexing agent for a period of time to keep the titanium nitride coating on the surface of the glass forming mold removed;
[0009] The mass ratio of the nitrilotriacetic acid complexing agent to the hydrogen peroxide is 1:100-20:100.
[0010] Preferably, the nitrilotriacetic acid complexing agent is one or more of nitrilotriacetic acid, nitrilotriacetic acid monosodium salt, nitrilotriacetic acid disodium salt, nitrilotriacetic acid trisodium salt, nitrilotriacetic acid monopotassium salt, nitrilotriacetic acid dipotassium salt, nitrilotriacetic acid tripotassium salt, nitrilotriacetic acid sodium potassium salt and hydrates thereof.
[0011] Preferably, the nitrilotriacetic acid complexing agent is nitrilotriacetic acid trisodium salt.
[0012] Preferably, the mass fraction of the hydrogen peroxide is 1-45%; the thickness of the titanium nitride coating in the glass forming mold is 1-20 μm, and the stainless steel component is one of 14Cr17Ni2, 06Cr19Ni10, and 1Cr18Ni9.
[0013] Preferably, the mass fraction of the hydrogen peroxide is 30%, and the mass ratio of the nitrilotriacetic acid complexing agent to the hydrogen peroxide is 9:100.
[0014] Preferably, the insulation reaction temperature is 0-80° C., and the reaction time is 1-720 min.
[0015] In the present invention, a method for recovering titanium element from the stripping liquid waste liquid obtained by the above-mentioned stripping method is provided, wherein the stripping liquid waste liquid is slowly evaporated to dryness, and then the obtained solid is annealed under a protective atmosphere to obtain a carbonate-titanium dioxide-porous carbon composite material, and carbonate crystals and titanium dioxide-porous carbon composite powder materials are obtained by washing, filtering and drying the filtrate; the waste liquid is a waste liquid obtained after stripping titanium nitride on the surface of a glass forming mold, and its components are a mixed liquid containing hydrogen peroxide, nitrilotriacetic acid-titanium ion complex, and sodium ions.
[0016] Preferably, the evaporation temperature is 25-95°C; the annealing temperature is 500-1000°C, the heating rate is 1-20°C / min, and the insulation time is 10-180min; and the protective atmosphere is nitrogen or argon.
[0017] Preferably, the evaporation temperature is 60° C.; the annealing temperature is 700° C., and the insulation time is 60 min.
[0018] Preferably, the filtered solid is titanium dioxide-porous carbon, which is vacuum dried at 30-120°C for 1-24h to obtain titanium dioxide-porous carbon composite material powder, and the filtrate is a carbonate solution, which can be evaporated and crystallized at 30-100°C to obtain carbonate crystals.
[0019] The stripping solution in the present invention is composed of hydrogen peroxide and nitrilotriacetic acid complexing agent, which has simple ingredients, low cost, and both components are non-toxic, easily degradable, and environmentally friendly. During the reaction, no strong base such as sodium hydroxide or potassium hydroxide is added. The nitrilotriacetic acid complexing agent can be quickly dissolved in the hydrogen peroxide solution, spontaneously creating a weak alkaline environment (pH=9) suitable for complexing and titanium ions. The dissolution process is heat-free and will not cause the decomposition of the oxidant, i.e. hydrogen peroxide. Therefore, the titanium nitride coating on the mold surface is quickly stripped and the weakly alkaline stripping solution does not corrode the surface of the stainless steel mold. The complexing agent trisodium nitrilotriacetate has no effect on Ti 4+The complexing capacity is 174 mg / g, which is higher than the same type of carboxylic acid complexing agents such as tetrasodium ethylenediaminetetraacetic acid (126 mg / g) and sodium gluconate (55 mg / g). In addition, the further waste liquid disposal process can realize the recovery of titanium elements and the prepared titanium dioxide-porous carbon composite powder material has potential application value in the fields of catalysis and energy storage, while the by-product carbonate (sodium carbonate, potassium carbonate) crystals can be directly used as raw materials for glass production.
[0020] Beneficial Effects
[0021] The method for removing titanium nitride coating on the surface of a glass forming mold disclosed in the present invention does not require the addition of strong alkali and is simple and efficient. The surface of the stainless steel mold after the removal is smooth and corrosion-free and can be recycled after repeated coating, which greatly reduces the production cost of glass products. In addition, the present application processes the waste liquid after the removal to achieve the recovery of titanium element and the preparation of titanium dioxide-porous carbon composite powder and carbonate, which is green and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The digital photos, scanning electron microscope images and corresponding element analysis comparison diagrams of the titanium nitride coating on the surface of the glass forming mold in Example 1 before and after removal;
[0023] Figure 2 The scanning electron microscope image and energy spectrum analysis image of the titanium dioxide-porous carbon prepared in Example 1;
[0024] Figure 3 The X-ray diffraction pattern of the sodium carbonate crystals obtained in Example 1;
[0025] Figure 4 The digital photos of the glass forming mold surface before and after the titanium nitride coating is removed in Comparative Example 1;
[0026] Figure 5 This is the scanning electron microscope image and elemental analysis of the titanium nitride coating on the surface of the glass forming mold obtained by the sodium hydroxide-hydrogen peroxide system in Comparative Example 1 before and after removal. DETAILED DESCRIPTION
[0027] The present invention is further described below in conjunction with specific embodiments. It should be understood that the following embodiments are only used to illustrate the implementation method of the present invention, and are not used to limit the operation and operating scope of the present invention, and the changes derived therefrom are still within the protection scope of the claims of the present invention.
[0028] Unless otherwise defined, all professional and scientific terms used in the present invention have the same meanings as those understood by technicians in the technical field of the present invention. Unless otherwise specified, the drugs or reagents used in the present invention are used in accordance with the product instructions or the conventional methods of use in the field. The process of the present invention is further described based on the drawings and specific embodiments of the specification.
[0029] Example 1
[0030] (1) Dissolve 1 kg of trisodium nitrilotriacetate in 10 L of 30% hydrogen peroxide to prepare a removal solution;
[0031] (2) Immersing the glass forming mold coated with titanium nitride coating in a stripping solution and reacting at 25°C for 1 hour can achieve complete stripping of the film layer. The stripping solution can be used repeatedly until the titanium nitride coating can no longer be stripped, and the waste stripping solution is collected;
[0032] (3) The collected waste liquid of the stripping liquid was placed in an evaporator and slowly evaporated to dryness at 60°C. The evaporated solid product was placed in a tubular furnace and heated to 700°C at a heating rate of 5°C / min under a nitrogen atmosphere and kept at this temperature for 60 min. After cooling, a sodium carbonate-titanium dioxide-porous carbon composite material was obtained.
[0033] (4) The sodium carbonate-titanium dioxide-porous carbon composite material is washed with deionized water and filtered to obtain a sodium carbonate solution and a titanium dioxide-porous carbon solid. The sodium carbonate solution is evaporated and crystallized at 60°C to obtain white sodium carbonate crystals. The titanium dioxide-porous carbon solid is vacuum dried at 60°C for 12 hours to obtain a black titanium dioxide-porous carbon composite material powder.
[0034] The effect of removing the titanium nitride coating on the surface of the glass forming mold in Example 1 was observed, and the digital photos, scanning electron microscope images and corresponding element analysis before and after removal were compared. Figure 1 As shown by Figure 1 It can be seen that after the stripping process, the golden titanium nitride coating of the glass forming mold disappeared, exposing the silvery white stainless steel mold surface. Further scanning electron microscope observation and element analysis results showed that after the stripping process, the titanium element on the stainless steel surface had completely disappeared, and the mold surface remained flat without corrosion.
[0035] The black titanium dioxide-porous carbon composite material powder obtained in Example 1 was subjected to scanning electron microscopy and energy spectrum analysis. The results are as follows: Figure 2 As shown, the X-ray diffraction pattern of white sodium carbonate crystals is as follows Figure 3 As shown, from Figure 2 and Figure 3It can be seen that Example 1 successfully achieved the recovery of titanium element and prepared titanium dioxide-porous carbon composite material. X-ray diffraction analysis of the white crystals after evaporation of the filtrate confirmed that the obtained crystals were pure phase sodium carbonate crystals.
[0036] Example 2
[0037] (1) Dissolve 1 kg of trisodium nitrilotriacetate in 10 L of 10% hydrogen peroxide to prepare a removal solution;
[0038] (2) Immersing the glass forming mold coated with titanium nitride coating in a stripping solution and reacting at 45°C for 1 hour can achieve complete stripping of the film layer. The stripping solution can be used repeatedly until the titanium nitride coating can no longer be stripped, and the waste stripping solution is collected;
[0039] (3) The collected waste liquid of the stripping liquid was placed in an evaporator and slowly evaporated to dryness at 40°C. The evaporated solid product was placed in a tubular furnace and heated to 650°C at a heating rate of 10°C / min under a nitrogen atmosphere and kept at this temperature for 60 min. After cooling, a sodium carbonate-titanium dioxide-porous carbon composite material was obtained.
[0040] (4) The sodium carbonate-titanium dioxide-porous carbon composite material is washed with deionized water and filtered to obtain a sodium carbonate solution and a titanium dioxide-porous carbon solid. The sodium carbonate solution is evaporated and crystallized at 70°C to obtain white sodium carbonate crystals. The titanium dioxide-porous carbon solid is vacuum dried at 50°C for 12 hours to obtain a titanium dioxide-porous carbon composite material powder.
[0041] Example 3
[0042] (1) Dissolve 1 kg of trisodium nitrilotriacetate in 10 L of 20% hydrogen peroxide to prepare a removal solution;
[0043] (2) Immersing the glass forming mold coated with titanium nitride coating in a stripping solution and reacting at 5°C for 4 hours can achieve complete stripping of the film layer. The stripping solution can be used repeatedly until the titanium nitride coating can no longer be stripped, and the waste stripping solution is collected;
[0044] (3) The collected waste liquid of the stripping liquid was placed in an evaporator and slowly evaporated to dryness at 80°C. The evaporated solid product was placed in a tubular furnace and heated to 800°C at a heating rate of 15°C / min under a nitrogen atmosphere and kept at that temperature for 35 minutes. After cooling, a sodium carbonate-titanium dioxide-porous carbon composite material was obtained.
[0045] (4) The sodium carbonate-titanium dioxide-porous carbon composite material is washed with deionized water and filtered to obtain a sodium carbonate solution and a titanium dioxide-porous carbon solid. The sodium carbonate solution is evaporated and crystallized at 55°C to obtain white sodium carbonate crystals. The titanium dioxide-porous carbon solid is vacuum dried at 40°C for 12 hours to obtain a titanium dioxide-porous carbon composite material powder.
[0046] Example 4
[0047] (1) Dissolve 1 kg of tripotassium nitrilotriacetate in 8 L of 30% hydrogen peroxide to prepare a removal solution;
[0048] (2) Immersing the glass forming mold coated with titanium nitride coating in a stripping solution, reacting at 50°C for 0.5h to achieve complete stripping of the film layer. The stripping solution can be used repeatedly until the titanium nitride coating can no longer be stripped, and the waste stripping solution is collected;
[0049] (3) The collected waste liquid of the stripping liquid was placed in an evaporator and slowly evaporated to dryness at 60°C. The evaporated solid product was placed in a tubular furnace and heated to 700°C at a heating rate of 5°C / min under a nitrogen atmosphere and kept at this temperature for 40 minutes. After cooling, a potassium carbonate-titanium dioxide-porous carbon composite material was obtained.
[0050] (4) The potassium carbonate-titanium dioxide-porous carbon composite material is washed with deionized water and filtered to obtain a potassium carbonate solution and a titanium dioxide-porous carbon solid. The potassium carbonate solution is evaporated and crystallized at 80°C to obtain potassium carbonate crystals. The titanium dioxide-porous carbon solid is vacuum dried at 60°C for 12 hours to obtain a titanium dioxide-porous carbon composite material powder.
[0051] Example 5
[0052] (1) Dissolve 0.5 kg of disodium nitrilotriacetate in 10 L of 10% hydrogen peroxide to prepare a removal solution;
[0053] (2) Immersing the glass forming mold coated with titanium nitride coating in a stripping solution and reacting at 35°C for 1 hour can achieve complete stripping of the film layer. The stripping solution can be used repeatedly until the titanium nitride coating can no longer be stripped, and the waste stripping solution is collected;
[0054] (3) The collected waste liquid of the stripping liquid was placed in an evaporator and slowly evaporated to dryness at 45°C. The evaporated solid product was placed in a tubular furnace and heated to 600°C at a heating rate of 5°C / min under a nitrogen atmosphere and kept at this temperature for 120 min. After cooling, a sodium carbonate-titanium dioxide-porous carbon composite material was obtained.
[0055] (4) The sodium carbonate-titanium dioxide-porous carbon composite material is washed with deionized water and filtered to obtain a sodium carbonate solution and a titanium dioxide-porous carbon solid. The sodium carbonate solution is evaporated and crystallized at 50°C to obtain sodium carbonate crystals. The titanium dioxide-porous carbon solid is vacuum dried at 60°C for 12 hours to obtain a titanium dioxide-porous carbon composite material powder.
[0056] Example 6
[0057] (1) Dissolve 2 kg of dipotassium nitrilotriacetate in 15 L of 15% hydrogen peroxide to prepare a removal solution;
[0058] (2) Immersing the glass forming mold coated with titanium nitride coating in a stripping solution and reacting at 40°C for 1 hour can achieve complete stripping of the film layer. The stripping solution can be used repeatedly until the titanium nitride coating can no longer be stripped, and the waste stripping solution is collected;
[0059] (3) placing the collected waste liquid of the stripping solution in an evaporator and slowly evaporating it to dryness at 60°C, placing the evaporated solid product in a tubular furnace, heating it to 900°C at a heating rate of 15°C / min under a nitrogen atmosphere and keeping it at that temperature for 20 minutes, and then cooling it to obtain a potassium carbonate-titanium dioxide-porous carbon composite material;
[0060] (4) The potassium carbonate-titanium dioxide-porous carbon composite material is washed with deionized water and filtered to obtain a potassium carbonate solution and a titanium dioxide-porous carbon solid. The potassium carbonate solution is evaporated and crystallized at 90°C to obtain potassium carbonate crystals. The titanium dioxide-porous carbon solid is vacuum dried at 60°C for 12 hours to obtain a titanium dioxide-porous carbon composite material powder.
[0061] Example 7
[0062] (1) Dissolve 0.6 kg of sodium potassium nitrilotriacetate in 10 L of 20% hydrogen peroxide to prepare a removal solution;
[0063] (2) Immersing the glass forming mold coated with titanium nitride coating in a stripping solution, reacting at 50°C for 0.5h to achieve complete stripping of the film layer. The stripping solution can be used repeatedly until the titanium nitride coating can no longer be stripped, and the waste stripping solution is collected;
[0064] (3) The collected waste liquid of the stripping liquid was placed in an evaporator and slowly evaporated to dryness at 50°C. The evaporated solid product was placed in a tubular furnace and heated to 800°C at a heating rate of 5°C / min under a nitrogen atmosphere and kept at that temperature for 60 min. After cooling, a sodium carbonate / potassium-titanium dioxide-porous carbon composite material was obtained.
[0065] (4) The sodium carbonate / potassium-titanium dioxide-porous carbon composite material is washed with deionized water and filtered to obtain a sodium carbonate / potassium solution and a titanium dioxide-porous carbon solid. The sodium carbonate / potassium solution is evaporated and crystallized at 85°C to obtain sodium carbonate / potassium crystals. The titanium dioxide-porous carbon solid is vacuum dried at 70°C for 6 hours to obtain a titanium dioxide-porous carbon composite material powder.
[0066] Example 8
[0067] (1) Dissolve 0.5 kg of trisodium nitrilotriacetate and 0.5 kg of tripotassium nitrilotriacetate in 8 L of 30% hydrogen peroxide to prepare a removal solution;
[0068] (2) Immersing the glass forming mold coated with titanium nitride coating in a stripping solution and reacting at 5°C for 4 hours can achieve complete stripping of the film layer. The stripping solution can be used repeatedly until the titanium nitride coating can no longer be stripped, and the waste stripping solution is collected;
[0069] (3) The collected waste liquid of the stripping liquid was placed in an evaporator and slowly evaporated to dryness at 70°C. The evaporated solid product was placed in a tubular furnace and heated to 500°C at a heating rate of 5°C / min under a nitrogen atmosphere and kept at this temperature for 180 min. After cooling, a sodium carbonate / potassium-titanium dioxide-porous carbon composite material was obtained.
[0070] (4) The sodium carbonate / potassium-titanium dioxide-porous carbon composite material is washed with deionized water and filtered to obtain a sodium carbonate / potassium solution and a titanium dioxide-porous carbon solid. The sodium carbonate / potassium solution is evaporated and crystallized at 50°C to obtain sodium carbonate / potassium crystals. The titanium dioxide-porous carbon solid is vacuum dried at 60°C for 12 hours to obtain a titanium dioxide-porous carbon composite material powder.
[0071] Comparative Example 1
[0072] 1 kg of sodium hydroxide (NaOH), tetrasodium ethylenediaminetetraacetate (EDTA-4Na), sodium citrate and phytic acid were used to replace the trisodium nitrilotriacetate in Example 1, respectively, and dissolved in 10 L of 30% by mass hydrogen peroxide to prepare a sodium hydroxide-hydrogen peroxide, tetrasodium ethylenediaminetetraacetate-hydrogen peroxide, sodium citrate-hydrogen peroxide and phytic acid-hydrogen peroxide stripping liquid system to strip the titanium nitride coating on the surface of the glass forming mold. The remaining steps were the same as in Example 1. The digital photos before and after stripping are shown in FIG. Figure 4 As shown, the results of scanning electron microscopy and elemental analysis after removal by sodium hydroxide-hydrogen peroxide system are as follows Figure 5 As shown. Figure 4 and Figure 5 It can be seen that under the same mass ratio, reaction temperature and time as those described in the embodiment, the removal effect is not good and the titanium nitride coating is still attached.
Claims
1. A method for removing titanium nitride coating on the surface of a glass forming mold, characterized in that: The glass forming mold with titanium nitride coating is immersed in a stripping solution composed of hydrogen peroxide and nitrilotriacetic acid complexing agent for a period of time until the titanium nitride coating on the surface of the glass forming mold is stripped; The mass ratio of the nitrilotriacetic acid complexing agent to hydrogen peroxide is 1:100 to 20:100; The nitrilotriacetic acid complexing agent is one or more of nitrilotriacetic acid, nitrilotriacetic acid monosodium salt, nitrilotriacetic acid disodium salt, nitrilotriacetic acid trisodium salt, nitrilotriacetic acid monopotassium salt, nitrilotriacetic acid dipotassium salt, nitrilotriacetic acid tripotassium salt, nitrilotriacetic acid sodium potassium salt and hydrates thereof; The temperature of the heat preservation reaction is 0-80° C., and the reaction time is 1-720 min.
2. The method for removing titanium nitride coating on the surface of a glass forming mold according to claim 1, characterized in that: The nitrilotriacetic acid complexing agent is nitrilotriacetic acid trisodium salt.
3. The method for removing titanium nitride coating on the surface of a glass forming mold according to claim 1, characterized in that: The mass fraction of the hydrogen peroxide is 1-45%; the thickness of the titanium nitride coating in the glass forming mold is 1-20 μm, and the stainless steel component is 14Cr 17 Ni2, 06Cr 19 Ni 10 1Cr 18 One of Ni9.
4. The method for removing titanium nitride coating on the surface of a glass forming mold according to claim 1, characterized in that: The mass fraction of the hydrogen peroxide is 30%, and the mass ratio of the nitrilotriacetic acid complexing agent to the hydrogen peroxide is 9:100.
Citation Information
Patent Citations
Removing liquid of titanium nitride film and method for removing titanium nitride film
CN101570860A
Environment-friendly decoating liquid for titanium-containing coatings and use method of environment-friendly decoating liquid
CN103046052A
Coating stripping powder for hard coating, prepared coating stripping liquid and coating stripping method
CN105018934A
Method for recycling titanic acid etching waste liquor and waste titanium material
CN107986326A
Coating removal solution for hard coating as well as preparation method and application thereof
CN109576719A